2021
DOI: 10.1111/jfbc.13842
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of a polysaccharide fraction from Craterellus cornucopioides in LPS‐stimulated macrophages

Abstract: Immunocytes‐involved inflammation is considered to modulate the damage in various diseases. Oxidative stress is initiated by oxidative agents such as LPS and ROS, which are strongly involved in chronic inflammation. Our previous study found that a polysaccharide fraction from Craterellus cornucopioides (CCPP‐1) showed good antioxidant activity. However, the anti‐inflammatory effect of CCPP‐1 was still elusive. The objective of this study was to evaluate the anti‐inflammatory activity of CCPP‐1 and its potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Together with phenolic compounds, polysaccharides are the most cited compounds in the composition of C. cornucopioides aqueous extracts. CCPs-1 and CCPs-2 are two water-soluble acidic polysaccharides with different contents of uronic acid, rhamnose, fucose, arabinose, xylose, mannose, glucose, and galactose [ 13 , 14 , 18 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Together with phenolic compounds, polysaccharides are the most cited compounds in the composition of C. cornucopioides aqueous extracts. CCPs-1 and CCPs-2 are two water-soluble acidic polysaccharides with different contents of uronic acid, rhamnose, fucose, arabinose, xylose, mannose, glucose, and galactose [ 13 , 14 , 18 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Activated macrophages release a large number of cytokines and pro‐inflammatory mediators, which cause oxidative stress, and finally lead to the occurrence of acute and chronic inflammatory diseases (Xu et al, 2021). The protein expression levels of pro‐inflammatory cytokines TNF‐ α , TGF‐ β , IL‐1 β , and IL‐6 were estimated by ELISA analysis to further study the anti‐inflammatory effects of EHP on LPS‐treated RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of anti-inflammatory, Sheng et al (2021) found that Lentinus edodes polysaccharides have antiinflammatory effects. Additionally, Craterellus cornucopioides polysaccharides showed anti-inflammatory effect by reducing the production of inflammatory mediators (iNOS) and the expression of pro-inflammatory factors (TNF-α, IL-1β and IL-18), which may be related to the inhibition of NF-κB signaling pathway (Xu et al, 2021a). For hyperlipidemia, Yu et al (2021) confirmed that Cordyceps militaris polysaccharides can alleviate hyperlipidemia by blocking preadipocyte differentiation.…”
Section: Introductionmentioning
confidence: 83%